Optical Performance of Single Point-Focus Fresnel Lens Concentrator System for Multiple Multi-Junction Solar Cells—A Numerical Study - Yassir A. Alamri; Saad Mahmoud; Raya Al-Dadah; Shivangi Sharma; J. N. Roy; Yulong Ding (Energies, 2021)
This paper investigates the potential of a new integrated solar concentrated photovoltaic (CPV) system that uses a solo point focus Fresnel lens for multiple multi-junction solar cells (MJSCs). The proposed system comprises of an FL concentrator as the primary optical element, a multi-leg homogeniser as the secondary optical element (SOE), a plano-concave lens, and four MJSCs. A three-dimensional model of this system was developed using the ray tracing method to predict the influence of aperture width, height, and position with respect to MJSCs of different reflective and refractive SOE on the overall optical efficiency of the system and the irradiance uniformity achieved on the MJSCs’ surfaces. The results show that the refractive homogeniser using N-BK7 glass can achieve higher optical efficiency (79%) compared to the reflective homogeniser (57.5%). In addition, the peak to average ratio of illumination at MJSCs for the reflective homogeniser ranges from 1.07 to 1.14, while for the refractive homogeniser, it ranges from 1.06 to 1.34, causing minimum effects on the electrical performance of the MJSCs. The novelty of this paper is the development of a high concentration CPV system that integrates multiple MJSCs with a uniform distribution of rays, unlike the conventional CPV systems that utilise a single concentrator onto a single MJSC. The optical efficiency of the CPV system was also examined using both the types of homogeniser (reflective and refractive).